Micropropagation of the caper in semi-solid medium and in temporary immersion bioreactors - Contreras Loera, Fabián; Chávez Ortiz, Lucía Isabel; Morales Domínguez, José Francisco; Pérez Molphe Balch, Eugenio (Revista Mexicana de Ciencias Agrícolas, 2021)
The objective was the development of an efficient system for the micropropagation of the caper (Capparis spinosa L.), a woody shrub of great interest due to its products, its remarkable resistance to drought and its tolerance to high temperatures. In vitro cultures were first established through disinfection and seed germination. A scarification of these with concentrated H2SO4 (98% v/v) was necessary to break dormancy. Only 15% of the seeds germinated. Nodal segments were obtained from the germinated seedlings, which were cultivated in basal medium of Murashige and Skoog (MS) semisolid added with benzyladenine (BA), 2-isopentenyladenine (2iP) and metatopoline (MT), this in order to induce multiple sprouting. The best response was obtained with 2 mg L-1 of these cytokinins, with an average number of well-differentiated sprouts per nodal segment of 3.6 with MT, 2.3 with BA and 1.5 with 2iP, this after 54 d of incubation. The combination of cytokinins with an auxin, naphthaleneacetic acid, was also tested. This combination improved the BA response, reaching an average of 3.2 sprouts per nodal segment. With the other cytokinins, it did not show a positive effect, maintaining very similar values with and without auxin. In addition to well-differentiated sprouts, masses or clusters of numerous small sprouts were generated, unsuitable for transfer to the rooting medium. These masses were transferred to RITA type temporary immersion bioreactors, where an average of 89 well-differentiated sprouts were generated per original explant, this in a medium with 1 mg L-1 of BA with 2 min immersions every 6 h. The sprouts took root with an efficiency of 80% in the basal environment, generating well-differentiated plants suitable for transfer to the ground. The survival already in the external environment of the plants generated in vitro was 85%, showing an apparently normal development already in ex vitro conditions.